Effect of Chemical and Organic Fertilizer Applications on Lettuce (Lactuca sativa L. var. crispa) Nitrate Accumulation - Eryilmaz Acikgoz, Funda (Asian Journal of Chemistry, 2010)
The nitrate content was analyzed in lettuce fertilized by urea as the chemical fertilizer, farm fertilizer and with different amounts of their mixture. At the end of the research, it was observed that different fertilizer applications had an important impact on the nitrate content of the lettuce. It was determined that the nitrate ratio was increased on the leaves of lettuce which were fertilized by urea and different mixture while nitrate content did not change in the leaves as a significant amount in the application of farm fertilizer.